Eksplorasi Pandangan dan Minat Generasi Y dan Z Terhadap Transformasi Koperasi - Sholihah, Dienni Ruhjatini; Lestari, Dea Delia; Dafina, Risty Rahma (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
Cooperatives have long been one of the main pillars of Indonesia's economy; however, interest among younger generations in this business model has declined in the digital era. The transformation of cooperatives through innovation and digitalization presents both challenges and opportunities in attracting the engagement of Generation Y and Z. This study aims to explore the factors influencing the perceptions and interest of these generations in cooperatives, focusing on digital innovation, social sustainability, and technological access. Employing a qualitative approach with a phenomenological design, this research involves semi-structured interviews with 15 participants from Generation Y and Z who have experience or interest in cooperatives. Thematic analysis is used to identify emerging patterns. The findings reveal that although Generation Y and Z show interest in cooperatives that embrace sustainability and digitalization, barriers such as limited understanding, negative experiences, and a lack of information about cooperatives persist. This study emphasizes the importance of innovation in cooperative products and services, as well as the need to enhance cooperative literacy and accessibility for younger generations. Therefore, cooperatives must adapt by leveraging digital technology and strengthening sustainability-based promotional strategies to remain relevant and appealing to Generation Y and Z.